Contemporary Liver Transplantation 2016
DOI: 10.1007/978-3-319-05543-5_40-2
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Liver Transplantation: Indications and Contraindications

Abstract: At the beginning of the third millennium, liver transplantation (LT) has turned from dream into a reality. Thomas E. Starzl, who first performed LT in March 1963, and many of his scholars allowed to live one of the most extraordinary adventures of modern medicine. Twenty years later, in 1983, the National Institute of Health Consensus Development Conference concluded that LT was "a promising alternative to current therapy in the management of late phase of several forms of serious liver diseases" and that it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 172 publications
0
9
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Especially in areas with organ shortages, the pendulum has largely swung away from expanded criteria for several reasons. These include an emphasis on performing LT in those HCC patients most likely to derive significant transplant survival benefit, 11 concerns that implementation of expanded tumor criteria could reduce access to LT for patients with better post-LT prognosis, 12,13 and longer wait times leading to increased use of local-regional therapy (LRT) as a bridge to LT. 14 There is also mounting evidence that tumor burden is just one of many factors that predict post-LT outcome. 15,16 In this context, selection criteria have begun to shift to include surrogates of tumor biology (eg, alpha-fetoprotein [AFP]) and response to LRT, with a number of pre-LT selection criteria recently proposed.…”
Section: Deceased Donor Lt For Hcc Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10] Especially in areas with organ shortages, the pendulum has largely swung away from expanded criteria for several reasons. These include an emphasis on performing LT in those HCC patients most likely to derive significant transplant survival benefit, 11 concerns that implementation of expanded tumor criteria could reduce access to LT for patients with better post-LT prognosis, 12,13 and longer wait times leading to increased use of local-regional therapy (LRT) as a bridge to LT. 14 There is also mounting evidence that tumor burden is just one of many factors that predict post-LT outcome. 15,16 In this context, selection criteria have begun to shift to include surrogates of tumor biology (eg, alpha-fetoprotein [AFP]) and response to LRT, with a number of pre-LT selection criteria recently proposed.…”
Section: Deceased Donor Lt For Hcc Selection Criteriamentioning
confidence: 99%
“…The question of offering LT to resectable, Child's A patients with single small HCC takes on greater importance after Berry and Ioannou 95 found that HCC patients derive a significantly lower survival benefit from LT than non-HCC patients. Further, several studies have shown that HCC patients with favorable tumor (single tumor <3 cm and AFP ≤20 ng/mL) and liver-related characteristics (Child's A cirrhosis and MELD-Na <15) 11,96,97 have reduced urgency for LT. Such patients who subsequently undergo LRT with complete radiographic response have a very low risk of waitlist dropout 11,96,98 and thus exceedingly low LT urgency with decreased LT survival benefit.…”
Section: Management Of Single Small Hcc Liver Transplantation Versusmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found a MELD >13, AFP < 1,000 ng/mL, and response to downstaging therapies to be highly associated with a benefit gain from transplantation while wait time and age had almost no impact on benefit. 67 Possibly future TBSs can be simplified by only including variables that actually have a major influence on transplant benefit. This is without placing too much weight on variables that may also increase posttransplant recurrence.…”
Section: Toward a Better Way To Select And Prioritize Hcc Patients For Liver Transplantation?mentioning
confidence: 99%
“…Lastly, models based on the concept of benefit have been recently created (12)(13)(14)(15). The transplant benefit represents a compromise between utility and priority, trying to define the group of patients better really obtaining a beneficial effect concerning survival after LT (16).…”
Section: Introductionmentioning
confidence: 99%